EDITING "THE COMPLETE CORRESPONDENCE" OF OCTAVE MIRBEAU - Michel, Pierre (Prace Polonistyczne, 2025)
Editing Octave Mirbeau’s complete correspondence is a long-term project that begun in 1967 and, as of 2023, has not yet been completely finished. Drawing on his experience as an academic editor, Pierre Michel examines different stages of his work as a researcher, highlighting the challenges faced in collecting and dating the letters. He outlines his editorial principles and underscores the significance of such an edition, not only for understanding the writer, his personality, and his career, but also the intellectual history of modern France.